2019
DOI: 10.1002/jssc.201900648
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for the investigation of two novel aminoalkanol derivatives of 1,7‐diethyl‐8,9‐diphenyl‐4‐azatricyclo[5.2.1.02,6] dec‐8‐ene‐3,5,10‐trione as potential anticancer drugs in water solution and serum

Abstract: A simple, rapid, capillary zone electrophoresis method was developed and validated for the analysis of two novel aminoalkanol derivatives (I) and (II) of 1,7-diethyl-8,9diphenyl-4-azatricyclo[5.2.1.0 2,6 ]dec-8-ene-3,5,10-trione, which were found in earlier studies as potential anticancer drugs. Samples were analyzed to demonstrate the specificity and stability indicating ability of the developed method. The samples were extracted using n-hexane-ethyl acetate mixture in the ratio of 90:10. Electrophoretic sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The synthesis, chemical characterization, and anticancer activity of the aforementioned compounds (I) and (II) were described previously in a patent application [36]. The present work is a continuation of our studies on aminoalkanol derivatives of dicarboximides [37][38][39][40][41]. In one of our previous studies, we developed a capillary electrophoresis (CE) method for analyzing the inhibition of tissue-non-specific alkaline phosphatase (TNAP) by the aminoalkanol derivatives of dimethyldicarboximide [38].…”
Section: Of 16mentioning
confidence: 99%
“…The synthesis, chemical characterization, and anticancer activity of the aforementioned compounds (I) and (II) were described previously in a patent application [36]. The present work is a continuation of our studies on aminoalkanol derivatives of dicarboximides [37][38][39][40][41]. In one of our previous studies, we developed a capillary electrophoresis (CE) method for analyzing the inhibition of tissue-non-specific alkaline phosphatase (TNAP) by the aminoalkanol derivatives of dimethyldicarboximide [38].…”
Section: Of 16mentioning
confidence: 99%
“…In our previous studies, we have shown that these derivatives (I, II, III, IV), apart from their primary antitumor activity, also inhibited the enzymatic activity of alkaline phosphatase [30], acid phosphatase [31] and acetylcholinesterase [32]. These derivatives were also previously investigated for their determination in biological material [33][34][35][36] and for their cytotoxicity on cancer cell lines such as K562 and HeLa cells [29]. In general, compounds with anti-cancer properties are of great interest in medicine, and their action may additionally affect the activity of many enzymes that protect against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were also investigated in our previous works on the possibility of their determination [ 38 , 39 , 40 , 41 ] and their inhibitory effect on alkaline phosphatase [ 42 ] and prostate acid phosphatase [ 43 ]. Interesting results described in our previous works [ 42 , 43 ] prompted us to conduct research on the influence of the mentioned aminoalkanol derivatives with potential anticancer activity on the enzymatic activity of acetylcholinesterase—an enzyme extremely important in our body.…”
Section: Introductionmentioning
confidence: 99%